1996
DOI: 10.1021/jp952744i
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Adsorption of Nonionic Surfactants:  Triton X-100 and C12E7 on Polystyrene Latex Particles Using Dynamic Light Scattering and Adsorption Isotherm Measurements

Abstract: The adsorption of the nonionic surfactants Triton X-100 and C12E7 on predominantly hydrophobic polystyrene latex particles has been examined as a function of surfactant concentration by measuring the hydrodynamic radius by dynamic light scattering and adsorption isotherms by a surface tension technique. The adsorption behavior of these materials differs significantly and is related to the structures of the surfactant “tails”. Adsorption of TX-100 most probably occurs in an approximately perpendicular geometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 69 publications
4
29
1
Order By: Relevance
“…Therefore, one could conclude that the contact point between PS particles should locate below the water surface. It has been reported that the adsorption of TX 100 occurred in an approximately perpendicular geometry and the surface of the PS particles was surrounded by poly (oxyethylene) chains [51]. Thereby it was reasonable to consider that the extended poly (oxyethylene) chains of TX 100 reduced the hydrophobic interaction force between PS particles.…”
Section: Effect Of Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one could conclude that the contact point between PS particles should locate below the water surface. It has been reported that the adsorption of TX 100 occurred in an approximately perpendicular geometry and the surface of the PS particles was surrounded by poly (oxyethylene) chains [51]. Thereby it was reasonable to consider that the extended poly (oxyethylene) chains of TX 100 reduced the hydrophobic interaction force between PS particles.…”
Section: Effect Of Surfactantmentioning
confidence: 99%
“…Previous investigations of the adsorption of TX 100 on particles, such as hydrophobic PS nanoparticles [51] and alkyl-grafted silica nanoparticles [52], indicated that TX 100 molecules were adsorbed on particle surfaces through the interaction between the hydrocarbon tail of the surfactant and the polymer chains, resulting in the conversion from the hydrophobicity to the hydrophilicity of particle surface state. To evaluate the effect of TX 100, an UV-vis absorption method was used to determine the amount of TX 100 adsorbed on PS particles surface.…”
Section: Effect Of Surfactantmentioning
confidence: 99%
“…Another method of analyzing the data consists of a more extended surfactant layer around the particles. Evidence for this type of behavior has been suggested in the literature (8). The sharp peak determining the number of ethylene oxide groups initially present in the solution.…”
Section: Resultsmentioning
confidence: 72%
“…Various techniques have been applied to measure the depletion effect: colorimetric titration methods (1)(2)(3)(4), static (5)(6)(7) and dynamic (8) surface-tension experiments, UV spectroscopy (9)(10)(11), fluorescence (12), and high-pressure liquid chromatography (13) [see also studies cited in Ref. (2)].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, to determine the surfactant adsorption one has also to measure the area of the solid-liquid interface per unit mass of the particles; the latter can be achieved by means of the BET-N 2 desorption method (9,11), dynamic light scattering (6,7), or electron microscopy (13).…”
Section: Introductionmentioning
confidence: 99%